Perancangan Company Profile Mycotech Melalui Media Booklet - Mulyana, Mulyana; Kurniawan, Ivan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
Global warming is a factor increasing the greenhouse effect gases. This is caused by human activities. One way to reduce this impact is to save energy in the construction sector by using environmentally friendly materials that can be recycled. Mycotech is a start-up that develops business from the mushroom biotechnology sector. Mycotech makes environmentally friendly building materials using mycelium as a natural adhesive. Therefore, Mycotech has an important role to continue to develop Mycotech products so that development industry players can switch to using environmentally friendly materials. By creating information media in the form of a Company Profile Booklet which contains information about Mycotech Company with the aim of attracting the interest of industry players to know more about the functions and benefits obtained.